2023
DOI: 10.1186/s12889-023-15603-0
|View full text |Cite
|
Sign up to set email alerts
|

The association of conspiracy beliefs and the uptake of COVID-19 vaccination: a cross-sectional study

Abstract: The COVID-19 pandemic revealed that health denialism might be an important determinant of adherence to preventive measures during epidemic challenges. Conspiracy beliefs seem to be one of the most visible manifestations of denialism in society. Despite intensive efforts to promote COVID-19 vaccinations, the number of citizens reluctant to get vaccinated was very large in many countries. The main aim of this study was the analysis of the association between the acceptance of the COVID-19 vaccination and conspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Unadjusted odds ratios (ORs) and adjusted odds ratios (AOR) with 95% confidence intervals (CIs) were reported by using simple and multiple logistic regressions, respectively. In the adjusted model, we included all Due to the fact that higher levels of conspiracy beliefs are associated with lower levels of attitude/willingness to receive COVID-19 vaccination 25,26 and increased vaccine hesitancy 27 as well that given the previous studies have used this variable as an independent variable in their mediation models, [25][26][27] the current study was regarded conspiracy beliefs as the independent variable in the mediation analysis. As well, previous studies have used health literacy as an independent variable, 28,29 and due to a significant bivariate relationship between health literacy and COVID-19 vaccination, we regarded health literacy as the independent variable in the mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Unadjusted odds ratios (ORs) and adjusted odds ratios (AOR) with 95% confidence intervals (CIs) were reported by using simple and multiple logistic regressions, respectively. In the adjusted model, we included all Due to the fact that higher levels of conspiracy beliefs are associated with lower levels of attitude/willingness to receive COVID-19 vaccination 25,26 and increased vaccine hesitancy 27 as well that given the previous studies have used this variable as an independent variable in their mediation models, [25][26][27] the current study was regarded conspiracy beliefs as the independent variable in the mediation analysis. As well, previous studies have used health literacy as an independent variable, 28,29 and due to a significant bivariate relationship between health literacy and COVID-19 vaccination, we regarded health literacy as the independent variable in the mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, we observed some propensity toward conspiracy beliefs, especially associated with vaccination. We had also previously marked a high prevalence of conspiracy beliefs regarding COVID-19 in Polish society [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies conducted during the COVID-19 pandemic confirmed this suggestion [ 5 ]. Conspiracy beliefs were a strong predictor of non-adherence to preventive measures, including COVID-19 vaccination [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Belief in COVID-19 conspiracy theories has exerted considerable influence on vaccination hesitancy. Previous studies found a strong positive correlation between conspiracy suspicions regarding the coronavirus and vaccine hesitancy, as an indicator of lower adherence to preventive measures ( 28 , 29 ). “Conspiracy beliefs” was one of the key factors associated with COVID-19 vaccine hesitancy, as revealed by a systematic review ( 30 ).…”
Section: Introductionmentioning
confidence: 99%